PENGARUH VARIASI MEDIA DAN JUMLAH TUMBUHAN TYPHA LATIFOLIA TERHADAP PENURUNAN KADAR BOD DAN COD PADA LIMBAH CAIR INDUSTRI TAHU DI SIDOARJO - Lily Oktavia; Mohammad Taufiq; Muchammad Tamyiz (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2021)
Sidoarjo Regency is one of the supporting districts of East Java province. Sidoarjo Regency is experiencing rapid progress because of the development and potential in trade and industry. One of the industries often found in Sidoarjo Regency is tofu factory. The rapid number of tofu craftsmen industry has caused an increase in the volume of liquid waste which also flows into water bodies. The purpose of this study was to determine the reduction in BOD and COD levels for the tofu factory wastewater treatment in the Sepande area, Sidoarjo Regency using a contructed wetland with Typha latifolia as the remediator. The research stage will be carried out using a laboratory scale using acclimatization as the adaptation stage of Typha latifolia and a crontructed wetland reactor as phytoremediation processing. Based on the results and discussion, it can be concluded that there was a decrease in BOD and COD levels in the tofu industrial wastewater in Sidoarjo using the Constructed Wetland system. The percentage reduction in BOD content was greatest in soil media with 3 stems of Typha latifolia plants and a detention time of 4 days of 72%. While the largest percentage reduction in COD levels was in soil media with 2 stems of Typha latifolia plants and 4 days of detention time of 84%.